First report of the chloroplast and mitochondrial genomes of the Indian pitcher plant, Nepenthes khasiana Hook.f. - Ruchishree Konhar; Debasis Dash; Devendra Kumar Biswal (BMC Research Notes)
Abstract Objectives Nepenthes, sometimes known as tropical pitcher plants or monkey cups, is a carnivorous plant genus that contains more than 160 species. Nepenthes khasiana, India's sole representative of the genus, is a rare and endangered dioecious plant endemic to North-east India. Despite the fact that it is a prominent insectivorous plant in the Nepenthaceae family, genomic resources for the species are limited, making genomic breeding and understanding the genetic basis of botanical carnivory difficult. Herein, we report the complete chloroplast (cp) and mitochondrial (mt) genomes of N. khasiana for the first time. These organelle genomes were assembled as part of a whole-genome sequencing project aimed at gaining deeper insights into their evolutionary relations with genomes of other carnivorous plants. Data description The complete cp genome (156,914 bp) and mt genome (900,031 bp) of N. khasiana are presented here. The cp genome contains two repeat regions and 131 genes (112 unique genes): 86 protein coding genes, 8 rRNA coding genes and 37 tRNA coding genes. The mt genome contains 84 genes (55 unique genes): 50 protein coding genes, 7 rRNA coding genes and 27 tRNA coding genes. The cp and mt genomic data generated will be useful for future molecular characterization and evolutionary research related to botanical carnivory.